Tunable Au–Ag nanobowl arrays for size-selective plasmonic biosensing. Issue 16 (25th April 2016) - Jana, Debrina; Lehnhoff, Emily; Bruzas, Ian; Robinson, Jendai; Lum, William; Sagle, Laura
Abstract : This paper describes the utilization of Au–Ag nanobowl arrays towards the size-selective detection of biological analytes, providing greater selectivity in complex media. Abstract : Selectivity is often a major obstacle for localized surface plasmon resonance-based biosensing in complex biological solutions. An additional degree of selectivity can be achieved through the incorporation of shape complementarity on the nanoparticle surface. Here, we report the versatile fabrication of substrate-bound Au–Ag nanobowl arrays through the galvanic ion replacement of silver nanodisk arrays. Both localized surface plasmon resonance (LSPR) and surface enhanced Raman spectroscopy (SERS) were carried out to detect the binding of analytes of varying size to the nanobowl arrays. Large increases in the LSPR and SERS response were measured for analytes that were small enough to enter the nanobowls, compared to those too large to come into contact with the interior of the nanobowls. This size-selective sensing should prove useful in both size determination and differentiation of large analytes in biological solutions, such as viruses, fungi, and bacterial cells.